Struktura české respektive československé státnosti v historickém pohledu - Pinz, Jan (Univerzita Pardubice, 1999)
The article named "The Structure of Czech, resp. Czechoslovak State Power in the Historical View" deals with the development of public pover arrangement (including theory of separation of powers) in general in ancient, medieval and New Age states. Special attention is paid to the history of public power in the Czech Kingdom, in the Republic of Czechoslovakia in the Czech Republic.
Keywords: Česko; Československo; stát; ústava; státnost; historie